2004
DOI: 10.1143/jjap.43.1631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Temperature on the Properties of Alq3 Amorphous Layers Prepared by Vacuum Deposition

Abstract: In this study, various Alq 3 amorphous layers are prepared by vacuum deposition at different substrate temperatures T sub . The surface morphology, structural information, and electrical and optical properties of these as-deposited layers are studied by atomic force microscopy, X-ray diffraction, J-E curves, and photoluminescence studies, respectively. The optimum deposition conditions for Alq 3 amorphous layers with respect to T sub are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…The phenomenon of increased PL intensity is in agreement with previous reports, which revealed that increasing the substrate temperature or annealing process for an AlQ 3 film could lead to a higher PL intensity, [26][27][28] except in the case of reduced intensity reported by Papadimitrakopoulos and co-workers. [29,30] Compared to curves c,d, the lower intensity of curve b can be attributed to incomplete transformation and less crystallization in 1 min.…”
Section: Full Papersupporting
confidence: 92%
“…The phenomenon of increased PL intensity is in agreement with previous reports, which revealed that increasing the substrate temperature or annealing process for an AlQ 3 film could lead to a higher PL intensity, [26][27][28] except in the case of reduced intensity reported by Papadimitrakopoulos and co-workers. [29,30] Compared to curves c,d, the lower intensity of curve b can be attributed to incomplete transformation and less crystallization in 1 min.…”
Section: Full Papersupporting
confidence: 92%
“…From a crystal grower's point of view, during PVD processes, both T sou and T sub markedly affect the qualities of the asdeposited films, and these effects were clearly exhibited by our earlier experimental results on C 60 polycrystalline films [19,20] and tris(8-hydroxyquinoline)aluminum (Alq 3 ) amorphous layers [21,22]. To extend these experimental findings from a single layer structure to a sophisticated and complicated optoelectronic heterostructure, the effects of T sou and T sub on the performance of OPV cells with a heterostructure of ITO/CuPc/C 60 /Ag prepared by PVD were studied.…”
Section: Introductionmentioning
confidence: 68%
“…Further details of the deposition processes have been presented elsewhere. 14 For electrical characterization, a top Au-metal contact with an active area of approximately 4 ϫ 4 mm 2 is fabricated by ion sputtering. A current-voltage ͑I-V͒ measurement is applied to the sandwiched Au/organic-layer/ITO configuration.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to obtain the actual magnitude of electric E field across the organic film, a correction with respect to the internal resistance of the measuring circuit is carefully taken into account. In low E fields from 0 to 0.75 MV/m, the measured current-density versus E field ͑J-E͒ curves of all of the samples exhibit linear Ohmic behavior, 14 from which the dark electrical conductivity of the organic Alq3 layer is then estimated. To eliminate effects from water vapor and oxygen gas, all the measurements are made after the sample is put into a cryostat system in dynamic vacuum for at least 12 h. During that period, data are taken to test their stability and reliability at 300 K. Experimental results reveal that, after 12 h in a dynamic vacuum, the dark electrical conductivities ͑T = 300 K͒ of the amorphous samples reach an almost steady state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation